2021
DOI: 10.7189/jogh.11.04054
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal pneumococcal carriage in South Asian infants: Results of observational cohort studies in vaccinated and unvaccinated populations

Abstract: Background Nasopharyngeal pneumococcal carriage (NPC) is a prerequisite for invasive pneumococcal disease and reduced carriage of vaccine serotypes is a marker for the protection offered by the pneumococcal conjugate vaccine (PCV). The present study reports NPC during the first year of life in a vaccinated (with PCV10) cohort in Bangladesh and an unvaccinated cohort in India. Methods A total of 450 and 459 infants were recruited from India and Bangladesh respectively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In this study, the most commonly detected NVSs were serotypes: 6C/6D, 19B/19C, and 15B/15C. The prevalence of these serotypes follows the changes reported in studies conducted in Bangladesh [ 35 ], the Netherlands [ 36 ], and Nigeria [ 37 ] following the introduction of PCV10. Additionally, the carriage of serotype 15 is known to be more prevalent in the PCV era [ 38 ].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the most commonly detected NVSs were serotypes: 6C/6D, 19B/19C, and 15B/15C. The prevalence of these serotypes follows the changes reported in studies conducted in Bangladesh [ 35 ], the Netherlands [ 36 ], and Nigeria [ 37 ] following the introduction of PCV10. Additionally, the carriage of serotype 15 is known to be more prevalent in the PCV era [ 38 ].…”
Section: Discussionsupporting
confidence: 67%
“…This study found a carriage rate of 48% in the Indian and 54.8% in the Bangladeshi cohort at 18 weeks, which increased to 53% and 64.8%, respectively, at 36 weeks. Vaccine serotypes for the same study was higher in the Indian cohort (17.8% vs. 9.8% for PCV-10 and 26.1% vs. 17.6% for PCV-13), with 6A, 6B, 19F, 23F, and 19A as the common serotypes [34].…”
Section: Discussionmentioning
confidence: 76%
“…In Cyprus, the non-vaccine serotypes detected in a study that included 1105 healthy children, aged between 6 and 36 months, were 15A, 6C, 23B, and 15B [ 39 ]. Among Bangladeshi children, 34, 15B, 17F, and 35B were the predominant non-vaccine serotypes, accounting for 43.6% [ 40 ]. The distribution of pneumococcal non-vaccine serotypes varies across studies due to many factors, such as age, country, study period, and time of vaccine introduction.…”
Section: Discussionmentioning
confidence: 99%